INVESTIGATION OF INDENTATION FRACTURE TOUGHNESS (K-IC) AND WEIBULL PARAMETERS OF 0.25Li(2)O.2SiO(2)-0.75BaO.2SiO(2) GLASS-CERAMIC - ÇETİNER, BURCU NİLGÜN; ERKMEN, ZİYA ENGİN (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST METALL & MATER SCI PAS, 2017)
In the present study, mechanical properties of 0.25Li(2)O.2SiO(2)-0.75BaO.2SiO(2) glass-ceramic were investigated. The transformations temperatures were determined by DTA instrument. The optimum nucleation temperature was found to be 540 degrees C. This suggested the crystallization temperatures as 675, 720 and 800 degrees C. After carrying out crystallization heat treatments, Vickers indentation test was applied. In order to determine the indentation fracture toughness (KIC), crack half-length, 'c' of the samples was measured. To calculate KIC, Young's modulus, E and the measured hardness, Hv were used. Using KIC and probability of fracture, 'P', ln ln[1/(1-P)]-ln KIC graph was drawn based on the Weibull distribution equation. Consequently, Weibull modulus,, m` and scale parameter, 'K-0' were determined and compared with each other.
Keywords: Lithium barium silicate glass-ceramic; Indentation Fracture Toughness; Hardness; Statistical Analysis; Weibull modulus; MECHANICAL-PROPERTIES; STRENGTH; P2O5; CRYSTALLIZATION; MICROSTRUCTURE; SYSTEM